Preparation method of stab-resistant and cutting-resistant mesh cloth for engineering transport vehicle
By mixing polyethylene powder, carbon fiber with paraffin oil and processing under high temperature and high pressure conditions, high-strength composite fibers are formed, and a stab-proof and cut-proof mesh is formed through multi-layer weaving and hot pressing technology, the problem of insufficient stab-proof and cut-proof performance in the existing technology is solved, and higher protection performance and durability are achieved.
Patent Information
- Application Number
- CN202510256669.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-18
AI Technical Summary
When the protective net of existing engineering transport vehicles faces sharp objects and complex transportation environments, the stabbing and cutting resistance performance is insufficient, making it difficult to provide continuous and effective protection, and traditional materials are prone to cracking or being cut.
The specific ratio of polyethylene powder, carbon fiber and paraffin oil is mixed with a specific ratio, stirring and dissolving under high temperature and high pressure conditions to form a uniform material liquid, and extruded and solidified through the spinneret, followed by multi-stage stretching and heat treatment to form high-strength, wear-resistant composite fibers. These fibers are woven by a multi-axial warp knitting machine to form a double-layer mesh structure and combined with epoxy resin and aramid fibers to form an integral structure through a hot pressing device.
It significantly improves the anti-spun and cut performance, durability and tensile strength of the material, can effectively resist puncture and cutting of sharp objects, reduce maintenance frequency and cost, while maintaining the lightweight design of the vehicle, improving fuel efficiency and operating flexibility.
Smart Images

Figure CN119843497A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of engineering transportation protection, and in particular to a method for preparing a puncture-proof and cut-proof mesh cloth for an engineering transportation vehicle. Background Art
[0002] In the field of engineering transportation, the safe transportation of goods is of vital importance. However, in actual operation, engineering transportation vehicles and their cargoes face a variety of potential risks, such as sharp objects, accidental collisions, etc., which may cause serious damage to the cargoes. Traditional protective measures, such as the use of ordinary protective nets or simple covering materials, although they can protect the cargoes to a certain extent, have obvious limitations, especially when facing obstacles with strong puncture and cutting capabilities, these traditional methods often seem to be powerless. For example, existing ordinary protective nets are usually made of polyester fibers or other synthetic fibers. Although such materials have certain strength and durability, they are easy to break or be cut when encountering sharp objects, thus failing to provide continuous and effective protection for the transport vehicles. In addition, some more complex transportation environments, such as construction sites and mines, increase the risk of damage to the cargoes due to the complex terrain and the presence of a large amount of uncleaned debris, and in more serious cases may also cause damage to the vehicle body.
[0003] In order to overcome the above problems, the market is in urgent need of a new type of protective material that can effectively prevent sharp objects from damaging vehicles and cargoes. Ideal protective materials should have the following characteristics: Excellent puncture and cut resistance: able to resist puncture and cutting by sharp objects under extreme conditions, ensuring the safety of key parts of the vehicle. Good flexibility and plasticity: easy to install and adapt to different shapes of vehicle structures without affecting the normal driving performance of the vehicle. Strong durability: able to withstand long-term use and wear, reducing maintenance frequency and cost. Lightweight design: minimize the additional load of the vehicle, improve fuel efficiency and operational flexibility. Summary of the invention
[0004] Purpose of the invention: In view of the shortcomings in the prior art, the present invention provides a method for preparing a puncture-proof and cut-proof mesh for an engineering transport vehicle.
[0005] Technical solution: The preparation method of the anti-puncture and anti-cut mesh for engineering transport vehicles provided by the present invention is as follows: 100 parts of polyethylene powder, 0.1-0.2 parts of carbon fiber and 400-450 parts of paraffin oil are mixed and placed in a high-pressure reactor, and stirred and dissolved for 4-6 hours at 180-190°C and 10±1MPa until a uniform liquid is formed. Under high temperature and high pressure conditions, polyethylene can be fully dissolved to form a uniform liquid, and a trace amount of carbon fiber is evenly dispersed therein, which enhances the overall mechanical properties of the material. Paraffin oil is used as a solvent to help polyethylene dissolve at high temperature and is removed in subsequent steps, so that polyethylene can solidify into a fiber form. The liquid is extruded through a spinneret into a coagulation bath containing ethanol, so that the paraffin oil in the liquid is rapidly diffused out, and the polyethylene is solidified into fibers. In the above process, ethanol rapidly absorbs paraffin oil, which prompts polyethylene to quickly solidify into fibers, ensuring the fineness and uniformity of the fibers, providing a basis for subsequent stretching, and also ensuring the consistency of fiber fineness and the smoothness of surface quality. Then, multi-stage stretching is performed at room temperature, with the total stretching being 15 times the original length. The stretched fiber is heat treated at 120-130°C for 30-40 minutes to further improve the crystallinity and orientation of the fiber. Multi-stage stretching increases the arrangement order of the molecular chain and improves the mechanical properties of the fiber; heat treatment further optimizes the crystal structure and enhances the strength and toughness of the fiber. It is then mixed with spandex and blended using a ring spinning machine to form a composite fiber with high toughness and a certain degree of elasticity.
[0006] The blended composite fiber is woven through a multi-axial warp knitting machine, and the weaving density is set to 10-15 fibers per centimeter to form a double-layer mesh structure. Each layer is arranged at 90 degrees to increase the stability of the structure. The machine speed is controlled to be maintained at 20-30 meters per minute to ensure that each fiber is evenly woven into the mesh cloth to obtain a high-strength fiber layer. This weaving method not only increases the stability and tear resistance of the material, but also improves the stability of the overall structure through the cross arrangement between the layers.
[0007] Place the high-strength fiber layer into the prepared impregnation liquid, ensuring that every corner is fully covered by the liquid. The immersion time is 5 to 6 minutes. During this period, gently shake the container to help penetration. Take it out of the impregnation liquid, place it on a flat surface, remove excess liquid and put it in an oven for curing. Set the temperature to 140°C and keep it warm for 45 minutes. After curing, cool it naturally at room temperature. During the curing process, the epoxy resin undergoes a cross-linking reaction to form a solid three-dimensional network structure, which greatly improves the hardness and durability of the material.
[0008] The aramid fiber is woven through a warp knitting machine with a weaving density of 20 fibers per inch to form a single-layer structure. The machine speed is controlled to be maintained at 10 meters per minute to ensure uniform weaving and obtain a wear-resistant layer.
[0009] On the workbench of the hot pressing equipment, lay the high-strength fiber layer, hot melt adhesive film, and wear-resistant layer from bottom to top, adjust the parameters of the hot pressing equipment, start the hot pressing equipment, melt the hot melt film and tightly combine it with the high-strength fiber layer and the wear-resistant layer, and take out the finished product after cooling to room temperature. Under high temperature and high pressure environment, the film melts and tightly combines with the upper and lower layers of materials to form an integral structure. This process not only ensures the bonding strength between the layers, but also improves the mechanical properties and stability of the entire composite material.
[0010] Specifically, the ratio of the stretched fiber to the aramid is 8:1-2. The spandex provides excellent elasticity, while the polyethylene fiber imparts high strength and wear resistance. The two are combined to form a composite fiber with high toughness and elasticity. Preferably, the ratio of the stretched fiber to the aramid is 8:2.
[0011] As a further improvement, during weaving, the blended composite fibers are woven through a multi-axial warp knitting machine, the weaving density is set to 10-15 fibers per centimeter, and the warp and weft angles are 45 degrees. This twill weaving method can effectively disperse stress, reduce local stress concentration, and enable the fibers to withstand tension in multiple directions, thereby improving the overall tensile strength of the material; the fine weaving structure can effectively prevent puncture and cutting by sharp objects. The machine speed is controlled to be maintained at 20-25 meters per minute to weave the first layer. The appropriate machine speed can ensure that the fiber will not be overstretched or relaxed during the weaving process, ensuring that each fiber can be evenly stressed, which helps to arrange the fibers neatly and without broken wires. When the first layer is woven to a certain length, the weaving machine is paused. A layer of aramid fiber is evenly laid on the woven mesh. Aramid fiber has extremely high strength and wear resistance, and can form an additional support layer inside the material, significantly improving the tensile strength and wear resistance of the overall structure. Restart the weaving machine and start weaving so that the second layer of mesh directly covers the aramid fiber layer to form a composite structure. Then continue to weave the third layer of mesh according to the same twill weaving parameters to ensure that the three layers of mesh are tightly combined. After completion, check whether there is broken wire or dislocation, and repair it in time to obtain a high-strength fiber layer. By precisely controlling the weaving process, the layers are seamlessly connected to form an overall structure, which enhances the stability and tear resistance of the material.
[0012] Specifically, the impregnation liquid is prepared by the following steps: 5 parts of epoxy resin and 1 part of curing agent are mixed evenly, and then 0.1 parts of toughening agent are added, and stirred until completely dissolved to obtain an impregnation liquid. More specifically, the epoxy resin is a glycidylamine epoxy resin, including AG-80 and TDE-85. The curing agent is methyltetrahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol. The toughening agent is a TPE type toughening agent, including SEBS and SBS. Preferably, 5 parts of TDE-85 and 1 part of methyltetrahydrophthalic anhydride are mixed evenly, and then 0.1 parts of toughening agent SEBS are added, and stirred until completely dissolved to obtain an impregnation liquid.
[0013] Specifically, the hot melt adhesive film is a polyamide PA hot melt adhesive film, a thermoplastic polyurethane TPU hot melt adhesive film, or a polyolefin elastomer POE hot melt adhesive film.
[0014] Specifically, the parameters of the hot pressing equipment are: the temperature is set to 180° C., the pressure is set to 3 MPa, and the heating time is 10 minutes.
[0015] Beneficial effects: The present invention adopts a specific proportion of polyethylene powder, carbon fiber and paraffin oil to mix, and stirs and dissolves under high temperature and high pressure conditions, so that the final formed fiber has extremely high strength and wear resistance. In particular, the crystallinity and orientation of the fiber are further improved through multi-stage stretching and heat treatment processes, which significantly enhances the material's ability to resist puncture and cutting by sharp objects. The composite fiber in the present invention is blended from polyethylene fiber and spandex, which gives the material excellent flexibility and a certain elasticity, making it easy to install on body structures of different shapes without affecting the normal driving performance of the vehicle. The raw materials used, such as polyethylene, spandex and aramid fibers, are all lightweight materials, which helps to reduce the additional load of the vehicle and improve fuel efficiency and operational flexibility.
[0016] The invention has a carefully designed preparation process, including multi-stage stretching, heat treatment, impregnation and curing steps, which ensures the high durability of the final product, can withstand long-term use and wear, and reduce maintenance frequency and cost. Further improvements in the weaving method can effectively disperse stress, reduce local stress concentration, and enable the fiber to withstand tension in multiple directions, thereby improving the overall tensile strength of the material. In addition, by weaving multiple layers and combining aramid fibers as a support layer, the stability and tear resistance of the overall structure are further improved.
[0017] The product prepared by the method of the present invention has good anti-cutting ability when facing sharp objects, is not easily cut, can provide sufficient protection for engineering vehicles, and reduces the risk of engineering vehicles being damaged during operation. At the same time, it has good durability, is not prone to wear and aging in long-term use, and does not need to be replaced frequently. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a sample picture of the mesh obtained in Example 1.
[0019] Figure 2 This is a physical picture of the product prepared from the mesh obtained in Example 3. DETAILED DESCRIPTION
[0020] The technical solution of the present application is described in detail below through examples, but the protection scope of the present application is not limited to the examples. The parts described in the present invention are all calculated by mass.
[0021] The following are embodiments to illustrate the scheme of the present invention in detail, but the protection scope of the present invention is not limited to the embodiments.
[0022] Example 1
[0023] Mix 100g polyethylene powder, 0.1g carbon fiber and 500ml paraffin oil (about 430g) and put them into a high-pressure reactor. Stir and dissolve at 180℃ and 10MPa for 4 hours until a uniform slurry is formed. Extrude the slurry through a spinneret into a coagulation bath containing ethanol, so that the paraffin oil in the slurry diffuses out quickly, and the polyethylene coagulates into fibers. Multi-stage stretching is performed at room temperature, and the total stretching is 15 times the original length. The stretched fibers are heat treated at 130℃ for 30 minutes to further improve the crystallinity and orientation of the fibers. Then mix it with spandex in a ratio of 8:2, and use a ring spinning machine for blending to form a composite fiber with high toughness and certain elasticity.
[0024] The blended composite fiber is woven through a multi-axial warp knitting machine, and the weaving density is set to 10-15 fibers per centimeter to form a single-layer structure. The machine speed is controlled to be maintained at 20-25 meters per minute to ensure that each fiber is evenly woven into the mesh cloth. After completion, check whether there is broken wire or dislocation, and repair it in time to obtain a high-strength fiber layer.
[0025] Mix TDE-85 and methyltetrahydrophthalic anhydride in a clean container and mix them evenly in a volume ratio of 5:1. Then add an appropriate amount of toughening agent TPE as needed and stir until completely dissolved. Arrange the above high-strength fiber layer in the prepared impregnation liquid to ensure that every corner is fully covered by the liquid. The soaking time is 5 minutes, and the container is gently shaken during the period to help penetration. Take out the sandwich structure cloth from the impregnation liquid, place it on a flat surface, remove excess liquid and put it in an oven for curing. Set the temperature to 140℃ and keep warm for 45 minutes. After curing, cool it naturally at room temperature and set it aside.
[0026] Use a multi-axial warp knitting machine and adjust the weaving density to 20 fibers per centimeter to form a single-layer structure. Weave the aramid fiber through the warp knitting machine and control the machine speed to maintain 10 meters per minute to ensure uniform weaving. After completion, check and repair any defects to obtain the wear-resistant layer for use.
[0027] Cut the thermoplastic polyurethane TPU film into a size that matches the high-strength fiber layer. Lay the high-strength fiber layer flat on the workbench of the hot press equipment, lay a layer of TPU film on top, and then lay the previously prepared wear-resistant layer. Adjust the parameters of the hot press equipment: set the temperature to 180°C, the pressure to 3MPa, and the heating time to 10 minutes. Start the hot press equipment to melt the TPU film and tightly combine it with the three layers of material. After cooling to room temperature, take it out. Samples such as Figure 1 shown.
[0028] The performance test results of the obtained product are as follows: tensile strength (radial): 1937N / 5cm; tensile strength (weft): 1550N / 5cm; tear strength (radial): 704N; tear strength (weft): 632N; bursting strength: 875N; abrasion resistance: <40mg / 1000cycles.
[0029] Conventional test results of ordinary mesh cloth: tensile strength (radial): 2442N / 5cm; tensile strength (weft): 2164N / 5cm; tear strength (radial): 471N; tear strength (weft): 381N; bursting strength: 657N; abrasion resistance: <40mg / 1000cycles.
[0030] Comparative Example 1 (Different impregnation liquids)
[0031] The basic steps of Comparative Example 1 are substantially the same as those of Example 1, except that the composition of the impregnation liquid is AG-80, the curing agent is 2,4,6-tris(dimethylaminomethyl)phenol, and the toughening agent is toughening agent SBS.
[0032] Comparative Example 2 (without impregnation step)
[0033] The basic steps of Comparative Example 2 are substantially the same as those of Example 1, except that the high-strength fiber layer is not impregnated.
[0034] The product performance comparison of Example 1 and the comparative example is shown in the following table:
[0035]
[0036] By comparing Example 1 of the present invention with conventional mesh, it can be seen that the present invention greatly improves the tear strength of the product, but has a small loss in tensile strength. By comparing the examples, it can be seen that Example 1 is superior to Comparative Example 1 in all aspects; the tear strength of Comparative Example 2 is not improved.
[0037] Further improvements are needed for the present invention to compensate for the loss of tensile strength.
[0038] Embodiment 2 (Improvement scheme)
[0039] Mix 100g polyethylene powder, 0.1g carbon fiber and 500ml paraffin oil (about 430g) and put them into a high-pressure reactor. Stir and dissolve at 180℃ and 10MPa for 4 hours until a uniform slurry is formed. Extrude the slurry through a spinneret into a coagulation bath containing ethanol, so that the paraffin oil in the slurry diffuses out quickly, and the polyethylene coagulates into fibers. Multi-stage stretching is performed at room temperature, and the total stretching is 15 times the original length. The stretched fibers are heat treated at 130℃ for 30 minutes to further improve the crystallinity and orientation of the fibers. Then mix it with spandex in a ratio of 8:2, and use a ring spinning machine for blending to form a composite fiber with high toughness and certain elasticity.
[0040] The blended composite fiber is woven through a multi-axial warp knitting machine, and the weaving density is set to 10-15 fibers per centimeter to form a double-layer mesh structure. Each layer is arranged at 90 degrees to increase the stability of the structure. The machine speed is controlled to be maintained at 20-25 meters per minute to ensure that each fiber is evenly woven into the mesh cloth. After completion, check whether there is broken wire or dislocation, and repair it in time to obtain a high-strength fiber layer.
[0041] Mix TDE-85 and methyltetrahydrophthalic anhydride in a clean container and mix them evenly in a volume ratio of 5:1. Then add an appropriate amount of toughening agent SEBS as needed and stir until completely dissolved. Arrange the above high-strength fiber layer in the prepared impregnation liquid to ensure that every corner is fully covered by the liquid. The soaking time is 5 minutes, and the container is gently shaken during the period to help penetration. Take out the sandwich structure cloth from the impregnation liquid, place it on a flat surface, remove excess liquid and put it in an oven for curing. Set the temperature to 140℃ and keep warm for 45 minutes. After curing, cool it naturally at room temperature and set it aside.
[0042] Use a multi-axial warp knitting machine and adjust the weaving density to 20 fibers per centimeter to form a single-layer structure. Weave the aramid fiber through the warp knitting machine and control the machine speed to maintain 10 meters per minute to ensure uniform weaving. After completion, check and repair any defects to obtain the wear-resistant layer for use.
[0043] Cut the thermoplastic polyurethane TPU film into a size that matches the high-strength fiber layer. Lay the high-strength fiber layer flat on the workbench of the hot press, lay a layer of TPU film on top, and then lay the previously prepared wear-resistant layer. Adjust the parameters of the hot press equipment: set the temperature to 180°C, the pressure to 3MPa, and the heating time to 10 minutes. Start the hot press equipment to melt the TPU film and tightly combine it with the three layers of material. After cooling to room temperature, take it out.
[0044] Embodiment 3 (Improvement scheme)
[0045] Mix 100g polyethylene powder, 0.1g carbon fiber and 500ml paraffin oil (about 430g) and put them into a high-pressure reactor. Stir and dissolve at 180℃ and 10MPa for 4 hours until a uniform slurry is formed. Extrude the slurry through a spinneret into a coagulation bath containing ethanol, so that the paraffin oil in the slurry diffuses out quickly, and the polyethylene coagulates into fibers. Multi-stage stretching is performed at room temperature, and the total stretching is 15 times the original length. The stretched fibers are heat treated at 130℃ for 30 minutes to further improve the crystallinity and orientation of the fibers. Then mix it with spandex in a ratio of 8:2, and use a ring spinning machine for blending to form a composite fiber with high toughness and certain elasticity.
[0046] The blended composite fiber is woven through a multi-axial warp knitting machine, the weaving density is set to 10-15 fibers per centimeter, the warp and weft angles are 45 degrees, the machine speed is controlled to be maintained at 20-25 meters per minute, and the first layer is woven to ensure that the fibers are arranged neatly and there is no broken wire phenomenon; when the first layer is woven to a certain length, the weaving machine is paused; a layer of aramid fiber is evenly laid on the woven mesh cloth, and the weaving machine is restarted so that the second layer of UHMWPE mesh cloth is directly covered on the aramid fiber layer to form a composite structure; then the third layer of mesh cloth is woven according to the same twill weaving parameters to ensure that the three layers of mesh cloth are tightly combined. After completion, check whether there is broken wire or dislocation, and repair it in time to obtain a high-strength fiber layer.
[0047] Mix TDE-85 and methyltetrahydrophthalic anhydride in a clean container and mix them evenly in a volume ratio of 5:1. Then add an appropriate amount of toughening agent SEBS as needed and stir until completely dissolved. Arrange the above high-strength fiber layer in the prepared impregnation liquid to ensure that every corner is fully covered by the liquid. The soaking time is 5 minutes, and the container is gently shaken during the period to help penetration. Take out the sandwich structure cloth from the impregnation liquid, place it on a flat surface, remove excess liquid and put it in an oven for curing. Set the temperature to 140℃ and keep warm for 45 minutes. After curing, cool it naturally at room temperature and set it aside.
[0048] Use a multi-axial warp knitting machine and adjust the weaving density to 20 fibers per centimeter to form a single-layer structure. Weave the aramid fiber through the warp knitting machine and control the machine speed to maintain 10 meters per minute to ensure uniform weaving. After completion, check and repair any defects to obtain the wear-resistant layer for use.
[0049] Cut the thermoplastic polyurethane TPU film into a size that matches the high-strength fiber layer. Lay the high-strength fiber layer flat on the workbench of the hot press, lay a layer of TPU film on top, and then lay the previously prepared wear-resistant layer. Adjust the parameters of the hot press equipment: set the temperature to 180°C, the pressure to 3MPa, and the heating time to 10 minutes. Start the hot press equipment to melt the TPU film and tightly combine it with the three layers of material. After cooling to room temperature, take it out.
[0050] The experimental data of Examples 1-3 are compared and are shown in the following table.
[0051]
[0052] From the comparison in the above table, it can be seen that the product obtained by the method described in Example 3 of the present invention has greatly improved tensile strength, tear strength and bursting strength. The mesh obtained in Example 3 is made into an anti-stab and anti-cut mesh for engineering transport vehicles (product such as Figure 2 It plays a good protective role during the use of engineering vehicles.
[0053] The above description is only a preferred embodiment of the present application and is not intended to limit the present application.
Claims
1. A method for preparing a stab-proof and cut-proof mesh for an engineering transport vehicle, characterized in that: 100 parts of polyethylene powder, 0.02-0.2 parts of carbon fiber and 400-450 parts of paraffin oil are mixed and put into a high-pressure reactor, and stirred and dissolved for 4-6 hours at a temperature of 180-190° C. and a pressure of 10±1 MPa until a uniform liquid is formed; the liquid is extruded through a spinneret into a coagulation bath containing ethanol, so that the paraffin oil in the liquid is rapidly diffused out, and the polyethylene is coagulated into fibers; then multi-stage stretching is performed at room temperature, and the total stretching is 14-16 times of the original length, and the stretched fiber is heat-treated at 120-130° C. for 30-40 minutes to further improve the crystallinity and orientation of the fiber, and then it is mixed with spandex, and blended using a ring spinning machine to obtain a composite fiber; The blended composite fiber is woven through a multi-axial warp knitting machine, and the weaving density is set to 10-15 fibers per centimeter to form a double-layer mesh structure. Each layer is arranged at 90 degrees and the machine speed is controlled to be maintained at 20-30 meters per minute to ensure that each fiber is evenly woven into the mesh cloth to obtain a high-strength fiber layer; The high-strength fiber layer is placed in the prepared impregnation liquid for 5 to 6 minutes, then taken out from the impregnation liquid, placed on a flat surface, and after removing excess liquid, placed in an oven for curing at a set temperature of 140 to 150°C for 45 to 60 minutes. After the curing is completed, it is naturally cooled at room temperature for standby use; The aramid fiber is knitted through a warp knitting machine with a knitting density of 15-20 fibers per centimeter to form a single-layer structure, and the machine speed is controlled to be maintained at 10-15 meters per minute to ensure uniform knitting and obtain a wear-resistant layer for standby use; On the workbench of the hot pressing equipment, lay the high-strength fiber layer, hot-melt adhesive film and wear-resistant layer in sequence from bottom to top, adjust the parameters of the hot pressing equipment, start the hot pressing equipment, melt the hot-melt film and tightly combine it with the high-strength fiber layer and the wear-resistant layer, and take out the finished product after cooling to room temperature.
2. The method for preparing the stab-proof and cut-proof mesh for engineering transport vehicles according to claim 1, characterized in that: The ratio of the drawn fiber to the aramid fiber is 8:1-2.
3. The method for preparing the stab-proof and cut-proof mesh for engineering transport vehicles according to claim 1, characterized in that: The blended composite fiber is woven through a multi-axial warp knitting machine, the weaving density is set to 10-15 fibers per centimeter, the warp and weft angles are 45 degrees, the machine speed is controlled to be maintained at 20-25 meters per minute, and the first layer is woven to ensure that the fibers are arranged neatly and there is no broken wire; then a layer of aramid fiber is evenly laid on the woven mesh, and the second layer is woven directly covering the aramid fiber layer to form a composite structure; then the third layer of mesh is woven according to the same twill weaving parameters to ensure that the three layers of mesh are tightly combined to obtain a high-strength fiber layer.
4. The method for preparing the stab-proof and cut-proof mesh for engineering transport vehicles according to claim 1, characterized in that: The impregnation liquid is prepared by the following steps: 5-8 parts of epoxy resin and 1-2 parts of curing agent are evenly mixed, and then 0.1-0.2 parts of toughening agent are added and stirred until completely dissolved to obtain the impregnation liquid.
5. The method for preparing the stab-proof and cut-proof mesh for engineering transport vehicles according to claim 4, characterized in that: The epoxy resin is a glycidylamine epoxy resin, including AG-80 and TDE-85.
6. The method for preparing the stab-proof and cut-proof mesh for engineering transport vehicles according to claim 4, characterized in that: The curing agent is methyltetrahydrophthalic anhydride and 2,4,6-tris(dimethylaminomethyl)phenol.
7. The method for preparing the stab-proof and cut-proof mesh for engineering transport vehicles according to claim 4, characterized in that: The toughening agent is a TPE type toughening agent, including SEBS and SBS.
8. The method for preparing the stab-proof and cut-proof mesh for engineering transport vehicles according to claim 4, characterized in that: 5 parts of TDE-85 and 1 part of methyltetrahydrophthalic anhydride were mixed evenly, and then 0.1 parts of toughening agent SEBS was added and stirred until completely dissolved to obtain an impregnation solution.
9. The method for preparing the stab-proof and cut-proof mesh for engineering transport vehicles according to claim 1, characterized in that: The hot melt adhesive film is polyamide PA hot melt adhesive film, thermoplastic polyurethane TPU hot melt adhesive film, polyolefin elastomer POE hot melt adhesive film.
10. The method for preparing the stab-proof and cut-proof mesh for engineering transport vehicles according to claim 1, characterized in that: The parameters of the hot pressing equipment are: the temperature is set to 180° C., the pressure is set to 3 MPa, and the heating time is 10 minutes.